Analysis of Adverse Drug Reactions in Patients with Diabetes Mellitus at Private clinics in Hyderabad, Pakistan - Hina Ayub, Muhammad Aslam Solangi, Mudassar Iqbal Arain, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes is characterized by hyperglycemia, a metabolic disorder resulting from defects in insulin secretion, action, or both. The traditional treatment choices available for diabetes include medications that are oral hypoglycemic agents and insulin. Due to the introduction of several medications during the past 20 years, the identification of adverse drug reactions has gained importance. Aim: The aim of this study was to evaluate the adverse drug reactions among diabetic patients and patients’ variables that were linked to the adverse drug reactions. Study Design: Cross-sectional study Place and Duration of Study: This research was done at private clinics in Hyderabad, Pakistan, from August 2021 to January 2022. Methodology: Three hundred and seventy seven participants and the data regarding baseline characteristics of participants, adverse drug reactions reported were analyzed together with the assessment of causality and severity of unwanted reactions. Results: Two hundred and forty one (63.9%) were males and 136 (36.1%) were females. Only 19 (5%) reported adverse drugs reactions. Hypoglycemia was the most commonly reported adverse drug reaction i.e.11 ((57.9%). On causality assessment, most of the adverse drug reactions fell under the category of probable adverse drug reaction i.e.15 (78.9%). Four (21.1%) of them had the doubtful relation with the medications. The majority of the adverse drug reactions that were reported by the participants were found to be moderately severe 13 (68.4%), when analyzed through severity assessment scale. Six (31.6%) were belonged to mildly severe category. Conclusion: The upper age group, male gender, and diabetes duration of more than 5 years were associated with a higher incidence of adverse drug reactions. This study gave in depth analysis of adverse drugs reactions reported in the patients of diabetes mellitus together with the nature of adverse drug reactions reported. A better patient outcome would result from the clinical pharmacist's active participation in adverse drug resistance. Keywords: Adverse drug resistance (ADR), Diabetes mellitus, Hypoglycemia, Severity